Halloween Holiday Grab Bag - Stamper, Judith Bauer; Girouard, Patrick (Troll Associates United States, 1993)
Discusses the origins of Halloween customs and suggests various activities for the holiday.
6 - 8 years
Keywords: Halloween decorations -- Juvenile literature; Halloween -- Juvenile literature; Cookery -- Juvenile literature